Microbial diversity of the soil, rhizosphere and wine from an emerging wine-producing region of Argentina - Rivas, Gabriel A. (2022)
The aim of this study was to characterize the microbial communities of Malbec vineyards recently established in a re-emerging wine region of Argentina. We studied the wine microbiota at different fermentation stages and the soil and rhizosphere microbial communities of two vineyards. A next-generation sequencing (NGS) approach was used to identify bacterial and fungal communities. The soil and rhizosphere samples showed a predominance of the phyla Proteobacteria and Actinobacteria. The order Rhizobiales stood out in the soil and rhizosphere of the two vineyards analyzed. Members of this order are recognized for their plant-growth promotion properties. Regarding fungal communities, Ascomycota and Basidiomycota were the most abundant phyla. The high abundance of the genus Ilyonectria in one of the vineyards may have impact on the health of vines. In wine samples, we detected low levels of lactic acid bacteria and the persistence of acetic acid bacteria (AAB) throughout the fermentation process, although there were no discernible effects on the acidity of wine. The results achieved could allow winemakers to improve the vineyard management practices and the fermentation process to favor the growth of microorganisms potentially beneficial for the health of the vines and the wine quality, while maintaining the regional microbial biodiversity.